Didactic resource to promote listening and speaking in teenagers. - Simbaña Montes, Cecilia del Carmen (2018)
The present research project has for object to know the process of teaching inside the classroom. Due to the students at “Nacional Saquisili” Educative Unit shows lack of interest at the time to learn, there are not classroom interactions, especially in speaking and listening practice. That is why; the principal objective is to determine teachers and students‟ perceptions about to use storytelling in promoting listening and speaking in teenagers at Nacional Saquisili Educative Unit. To make possible this study was applied an interview to 4 teacher and 15 students of the second year of bachelor. The interview consisted in bank question of 6 semi-structured items. It permitted to identify strengths and weaknesses in teaching Listening and Speaking in English language. The result was analyzed using descriptive method that permitted to define and classify all conclusions about application of interviews. Furthermore, it applied the bibliographic research that allowed to obtain information about theoretical framework. As a result the teacher did not use didactic resources focused in the development of two skills. Also the English teacher only used book providing by Ministerio de Educación. However, students prefer to learn using different didactic materials. Finally, with theoretical framework and all analysis obtained of the teachers and students; they agree using the storytelling as a useful tool with genuine materials promoting comprehension and class interaction. Of this way it resource generates an interactive and dynamic environment promoting the communication training inside and outside the classroom.